Topics in Applied Physics
DOI: 10.1007/3-540-44552-8_9
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Infrared Absorption

Abstract: Abstract. Molecules adsorbed on metal island films or particles exhibit 10-1000 times more intense infrared absorption than would be expected from conventional measurements without the metal. This effect is referred to as surface-enhanced infrared absorption (SEIRA) to emphasize the similarities with surface-enhanced Raman scattering (SERS). The electromagnetic interactions of the incident photon field with the metal and molecules play predominant roles in this effect. The chemical interactions of the molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
289
2
1

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(297 citation statements)
references
References 90 publications
(206 reference statements)
5
289
2
1
Order By: Relevance
“…41 The chemical mechanism in SEIRA is less well understood but is thought to relate in a similar manner. 32 Considering the expected change in chemical environment upon SAM formation and particularly its dependence on thiol chemisorption, the similarity in the extrinsic enhancement factor ͑3ϫ͒ relative to metal-based observations suggests that a related chemical mechanism may exist on the semiconductor surface. It is hoped that our results will add to the data supporting such effects and to corresponding refinements in theoretical hypotheses.…”
Section: -5mentioning
confidence: 97%
See 2 more Smart Citations
“…41 The chemical mechanism in SEIRA is less well understood but is thought to relate in a similar manner. 32 Considering the expected change in chemical environment upon SAM formation and particularly its dependence on thiol chemisorption, the similarity in the extrinsic enhancement factor ͑3ϫ͒ relative to metal-based observations suggests that a related chemical mechanism may exist on the semiconductor surface. It is hoped that our results will add to the data supporting such effects and to corresponding refinements in theoretical hypotheses.…”
Section: -5mentioning
confidence: 97%
“…For example, chemisorption has been demonstrated as a distinguishing feature of IR enhancement on planar metal surfaces, such as the four times increase in vibrational polarizability observed for CO chemisorbed on Cu and Ag, compared to its gas and physisorbed phases. 37,38 Moreover, enhancements of the order 10-10 3 can be realized on rough metal or metal-particle substrates in surface enhanced infrared absorption ͑SEIRA͒ techniques, 32 and has been observed for n17 adsorbed on Au islands specifically. 39 Both electromagnetic ͑plasma resonance͒ and chemical mechanisms account for the observed SEIRA enhancements and research distinguishing the two has been reported, 32,40 concluding that ͑1͒ scaling of order 10 can be achieved based on the chemical mechanism and that ͑2͒ chemisorption is a required element for this to manifest.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with the IRRAS technique, which is characterized by the presence of a thin solution layer in the optical path, surface enhanced infrared absorption spectroscopy (SEIRAS) in the internal attenuated total reflection (ATR) configuration [35,36] provides many advantages for equilibrium and time resolved in situ studies at electrochemical interfaces. These advantages are threefold: (1) high and specific surface sensitivity of the IR response with an enhancement factor up to about 100; (2) dominant first layer effect with a probing range of a few nanometers; (3) no limitation of the mass transport and perturbation of potential distribution.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, sensing using MIF is typically based on shift of the maximum of the SPR band upon changes of dielectric environment. In addition, the strong near field enhancement taking place close to the island surface, allows amplification of Raman signal [3][4][5][6] or infrared absorption [7][8][9][10] of closely located molecules. The near field enhancement is largest for very small particles and inter-particle distances, which are typically few nanometers in the case of MIF.…”
Section: Introductionmentioning
confidence: 99%